2002
DOI: 10.1017/s1350482702003055
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of precipitation associated with a western disturbance using a high‐resolution regional model: role of parameterisation of physical processes

Abstract: In this study a non-hydrostatic version of the PSU/NCAR Betts-Miller (or Grell) schemes as PBL and convection parameterisation schemes respectively are best compared to the other schemes used in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…Previous studies have found that mesoscale simulations over the High-Asia mountains may agree well with the limited observations available [e.g., Azadi et al, 2001;Lang and Barros 2004;Barros et al, 2006]. In particular, the Weather Research and Forecasting (WRF) model has been shown to be capable of accurately simulating known patterns of extreme precipitation in the High-Asia mountains [Sato et al, 2008;Li et al, 2009;Maussion et al, 2011Maussion et al, , 2014Sato 2013] and in other high mountains around the world [e.g., Rasmussen et al, 2011;Jiménez et al, 2013;Viale et al, 2013].…”
Section: Introductionmentioning
confidence: 79%
“…Previous studies have found that mesoscale simulations over the High-Asia mountains may agree well with the limited observations available [e.g., Azadi et al, 2001;Lang and Barros 2004;Barros et al, 2006]. In particular, the Weather Research and Forecasting (WRF) model has been shown to be capable of accurately simulating known patterns of extreme precipitation in the High-Asia mountains [Sato et al, 2008;Li et al, 2009;Maussion et al, 2011Maussion et al, , 2014Sato 2013] and in other high mountains around the world [e.g., Rasmussen et al, 2011;Jiménez et al, 2013;Viale et al, 2013].…”
Section: Introductionmentioning
confidence: 79%
“…Chakravortty and Basu, 1957;Mooley, 1957;Sharma and Subramaniam, 1983;Rangachary and Bandyopadhyay, 1987;Lang and Barros, 2004;Roy and Roy Bhowmik, 2005;Kotal et al, 2014;Dimri et al, 2015) and have been the subject of a number * http://imd.gov.in/section/nhac/wxfaq.pdf of modelling case studies (e.g. Ramanathan and Saha, 1972;Chitlangia, 1976;Gupta et al, 1999;Azadi et al, 2002;Dimri, 2004;Semwal and Dimri, 2012;Dimri and Chevuturi, 2014;Patil and Kumar, 2016). Despite the abundant interest in these systems, little headway has been made in developing a systematic understanding of them.…”
Section: Introductionmentioning
confidence: 99%
“…We tested several model settings (Chang et al, 2005) and selected a configuration with the MRF planetary boundary layer (PBL) scheme, the Dudhia shortwave radiation scheme, and the Goddard longwave radiation scheme with the Grell-Devenyi ensemble convective parameterization (CP) scheme as the control simulation. The choice of the control configuration was also guided by some recent high resolution model simulations over the Indian region (Azadi et al, 2002;Xavier et al, 2006).…”
Section: Model Configuration and Experimental Set Upmentioning
confidence: 99%